Silica sol precision casting process
By improving the wax mold treatment, mold shell preparation and post-treatment processes, the wax mold treatment, insufficient bonding strength of mold shell, low dewaxing efficiency and complex post-treatment in the traditional silicon sol casting process are solved, and efficient production of high-precision castings is achieved and cost is reduced.
Patent Information
- Application Number
- CN202510599063.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-10
- Publication Date
- 2025-08-26
AI Technical Summary
In the traditional silicon sol casting process, the wax mold processing is not thorough, the mold shell bonding strength is insufficient, the dewaxing efficiency is low, the baking breathability is poor and the post-processing is complicated, resulting in low yield and high cost of castings, which is difficult to meet the high-precision needs.
Through improved wax mold treatment (standard-evaporation-decontamination-curing), mold shell preparation (layered sand sprinkler and slurry) and post-treatment (high-pressure steam dewaxing, roasting temperature control, passivation treatment), the wax mold quality, mold shell performance and casting surface quality are optimized.
The quality of the wax mold and mold shell is significantly improved, the dewaxing time is shortened, the residual amount is reduced, the accuracy and surface finish of the castings are improved, the production cost is reduced, and the yield and production efficiency are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of precision casting, and in particular relates to a silica sol precision casting process. Background Art
[0002] The traditional silica sol casting process has the following problems: 1. The wax material is not completely dehydrated during the wax model processing, resulting in uneven shrinkage of the wax model and increased surface defects; 2. The bonding strength of the layered coating of the shell is insufficient, which is prone to cracks or sand falling, affecting the accuracy of the casting; 3. The dewaxing efficiency is low and easy to remain, and the air permeability of the shell after baking is poor; 4. The post-processing process is complicated, the surface cleaning of the casting is not thorough, and the passivation and heat treatment effects are unstable.
[0003] The above problems result in low casting yield and high cost, making it difficult to meet high-precision casting requirements. Summary of the Invention
[0004] The purpose of the present invention is to provide a silica sol precision casting process in view of the existing problems.
[0005] The present invention is achieved through the following technical solutions: A silica sol precision casting process, characterized by comprising the following steps: (1) Wax model preparation 1) Wax treatment: 1. Dehydration in standing barrel I: let the old wax liquid recovered from dewaxing stand at 85-90℃ for 6-8 hours to remove more than 90% of free water; 2. Evaporation in water removal barrel: Mechanically stir at 110-120℃ for 10-12h (speed 30-50r / min) to evaporate the residual water until the wax liquid moisture content is less than 0.1%; 3. Standing barrel II decontamination: Standing at 80-85℃ for ≥12h to separate suspended impurities; 4. Curing in an insulation box: Keep warm at 54±2℃ for ≥24h to ensure uniform distribution of wax molecules and a final shrinkage rate of ≤0.5%.
[0006] 2) Wax mold pressing: use injection pressure of 4.2MPa, holding time of 5-15s, wax cylinder temperature of 54±2℃, wax injection nozzle temperature of 57-64℃, cooling water temperature after pressing <10℃, and ensure that the dimensional error of the wax mold is ≤±0.1mm.
[0007] 3) Module welding: wax pattern spacing is 6-8mm (10-12mm for parts with holes / grooves), inner gate length is 8-12mm, and the distance between the upper edge of the gate cup and the wax pattern is ≥60mm. After welding, the module is impregnated with ZF-301 cleaning agent (room temperature 24±3℃) and blown dry to ensure that the silica sol wettability test is qualified.
[0008] (2) Shell preparation 1) Coating preparation: 1. Surface coating: Silica sol (S830 type) and zircon powder are mixed in a mass ratio of 10: (30-36), with a flow cup viscosity of 50±5s (4# measuring cup); 2. Transition layer coating: silica sol (S1430 type) and Shangdian powder are mixed at a ratio of 10: (16-17), with a viscosity of 20±2s; 3. Back coating: Silica sol and Shangdian powder are mixed at a ratio of 10: (14-15), with a viscosity of 13±1s.
[0009] 2) Layered shell making: 1. Surface layer: Sprinkle 80-120 mesh zircon sand, drying time ≥ 6h (humidity 50-70%, temperature 24±2℃); 2. Transition layer: Sprinkle 50-100 mesh zircon sand or 40-70 mesh shop sand, drying time ≥ 8h; 3. Back layer: sprinkle 16-30 mesh sand, drying time ≥ 12h; 4. Sealing layer: Use low viscosity silica sol (viscosity 6-8s) to seal surface pores.
[0010] (3) Dewaxing and shell firing 1) High-pressure steam dewaxing: steam pressure 0.6-0.75MPa, dewaxing time 6-8min, ensuring wax residue <0.05%; 2) Firing: 1150℃ for ordinary parts, 1175℃ for complex parts, 1195℃ for special parts, keep warm for ≥30min, the shell will be white or rose color.
[0011] (4) Melting and pouring 1) Alloy smelting: Calculate the charge ratio according to the element burnout rate (carbon 3-5%, silicon 10%), the smelting temperature is 1580-1600℃, and add 0.1-0.3% aluminum for final deoxidation after refining; 2) High temperature pouring: The mold shell is maintained at 700-850℃, covered with charcoal or graphite powder during pouring, and the pouring pressure matches the wall thickness of the casting (thin-walled parts are increased to 0.4MPa).
[0012] (5) Post-processing 1) Cutting gate: The gate allowance for grinding wheel cutting is ≤2mm (3-5mm for precision cutting); 2) Shot blasting: Use 0.2mm steel shot for blasting, and alkali explosion process for complex inner cavity (700℃ alkali solution treatment ≥20min); 3) Passivation treatment: Immerse in HNO3:HF:H2O=6:5:5 mixture (55-65℃) for 2-5 minutes, rinse with water three times and then blow dry; 4) Heat treatment: Sealed annealing in an iron box (add charcoal to prevent oxidation), furnace cooling to 600℃ and then air cooling to eliminate internal stress.
[0013] (6) Correction and trimming 1) Use hot calibration (500-600℃) or cold calibration tooling to correct deformation; 2) Grind the surface with a belt machine until the flat surface residue is less than 0.2mm, the curved surface is less than 0.1mm, and the roughness Ra is less than 3.2μm.
[0014] Compared with the prior art, the present invention has the following advantages: 1. Significantly improved wax pattern quality: A phased gradient treatment (standing - evaporation - decontamination - maturation) is used to reduce the moisture content of the wax material from 0.5-1.0% in the traditional process to <0.1%, the shrinkage rate of the wax pattern is reduced from 1.2-1.8% to ≤0.5%, the surface finish Ra ≤1.6μm, and the bubble defect rate is reduced from 8-10% to <1%. The module welding accuracy is improved, the wax pattern spacing error is controlled within ±0.1mm, and the welding gap rate is reduced to 0.3% (2-3% in the traditional process).
[0015] 2. Optimization of the overall performance of the mold shell: The surface layer of zircon powder coating (cup viscosity 50±5s) combined with 80-120 mesh zircon sand increases the flexural strength of the mold shell from 4-5 MPa in the traditional process to ≥6 MPa. The back layer of coarse-grained upper sand (16-30 mesh) and the sealing process improve the air permeability of the mold shell by 30%, and the porosity of the casting is reduced from 5% to <1%. The layered gradient sand spreading (zircon sand → upper sand transition) reduces the cracking rate of the mold shell after roasting at 1175°C from 15% to <3%.
[0016] 3. Dual optimization of dewaxing efficiency and mold shell quality: High-pressure steam dewaxing (0.6-0.75MPa) shortens the dewaxing time from the traditional 20-30 minutes to 6-8 minutes, and reduces the wax residue from 0.2-0.5% to <0.05%. The roasting temperature is controlled in stages (1150℃ for ordinary parts / 1175℃ for complex parts / 1195℃ for special parts), and the high-temperature strength of the mold shell is increased by 25%. The dimensional accuracy of the casting reaches CT6 (traditionally CT7-8).
[0017] 4. Breakthroughs in post-processing efficiency and surface quality: Residual sand removal rate > 99%: The alkali explosion process (700°C alkali solution treatment ≥ 20 minutes) combined with shot blasting (0.2mm steel shot) reduces sand removal time in complex cavities by 50%; uniform passivation effect: After passivation with an HNO3:HF:H2O mixture, the salt spray resistance test time of the casting surface is extended from 24 hours to 72 hours, meeting ISO 9227 standard level 9; the iron box sealed annealing process reduces casting deformation to ≤ 0.05mm / m and reduces hardness uniformity deviation from ±15HB to ±5HB.
[0018] 5. Outstanding cost and environmental benefits: Through decontamination using a static barrel II and aging in an insulated box, the reuse rate of old wax has increased from 3-5 times to over 10 times, reducing raw material costs by 40%. The number of shell layers has been reduced by 30% (conventional 6-8 layers → this invention's 4-5 layers), total drying time has been shortened by 25%, and overall energy consumption has been reduced by 20%. The recycle period of the ZF-301 cleaning agent has been extended to 40 days (conventional cleaning agents use 15-20 days), and waste liquid emissions have been reduced by 60%. DETAILED DESCRIPTION
[0019] Example 1: Aviation thin-walled casting (material: Z22-1 cast iron) (1) Wax model preparation 1) Wax treatment: 1. Dehydration in standing barrel I: The old wax liquid is placed at 85℃ for 8 hours, and the sediment at the bottom is drained, and the free water content is reduced to 1.2%; 2. Evaporation in water removal barrel: the temperature is raised to 115°C, mechanical stirring (speed 40r / min) for 12 hours, and the water content of the wax liquid after evaporation is 0.08%; 3. Standing barrel II decontamination: Standing at 80℃ for 14 hours to separate impurity particles (diameter > 50μm); 4. Curing in an incubator: Keep at 54±1℃ for 26 hours, the shrinkage of the wax is 0.45% (test method: ASTM D790).
[0020] 2) Wax mold pressing: Use an injection pressure of 4.2MPa, a holding time of 10 seconds, a wax cylinder temperature of 54±1℃, and a wax nozzle temperature of 60℃; the cooling water temperature is 8℃. The dimensional error of the wax mold after demolding is ±0.08mm (detected by a three-dimensional coordinate measuring machine); there are no bubbles or flash on the surface, and the surface finish is Ra 1.6μm (roughness tester Mitutoyo SJ-410).
[0021] 3) Module welding: wax mold spacing 7mm (10mm for the hole part), inner gate length 10mm, gate cup upper edge 65mm away from wax mold; welding gap rate 0.2% (microscope detection), immersed in ZF-301 cleaning agent 3 times (1 second each time), after drying, the wettability of silica sol is qualified.
[0022] (2) Shell preparation 1) Coating preparation: 1. Surface layer: 10kg silica sol (S830 type) + 33kg zircon powder, flow cup viscosity 52 seconds (4# flow cup, GB / T1723); 2. Transition layer: 10kg silica sol (S1430 type) + 16.5kg powder, viscosity 21 seconds; 3. Back layer: 10kg silica sol + 14.5kg powder, viscosity 13.5 seconds.
[0023] 2) Layered shell making: 1. Surface layer: Sprinkle 100 mesh zircon sand (particle size distribution 80-120 mesh), dry for 7 hours (humidity 60%, temperature 24±1℃); 2. Transition layer: sprinkle 60 mesh sand (particle size 40-70 mesh) and dry for 9 hours; 3. Back layer: sprinkle 20 mesh shop sand (particle size 16-30 mesh) and dry for 13 hours; 4. Sealing layer: Silica sol (viscosity 7 seconds) seals surface pores.
[0024] (3) Dewaxing and roasting 1) High-pressure steam dewaxing: steam pressure 0.7 MPa, dewaxing time 7 minutes, wax residue 0.03% (gravimetric detection); 2) Firing: Keep at 1175℃ for 35 minutes, the shell is white and has no cracks (visual and penetrant inspection).
[0025] (4) Melting and pouring 1) Alloy smelting: Z22-1 cast iron (C 4.2%, Si 2.05%, Mn 0.35%), smelting temperature 1590±10℃; after refining, add 0.2% aluminum for final deoxidation.
[0026] 2) High temperature pouring: mold shell temperature 800℃, pouring pressure 0.3MPa, covered with charcoal for shrinkage feeding; the casting surface has no cold shut and air holes, and the dimensional accuracy is CT6 level (GB / T 6414).
[0027] (5) Post-processing 1) Cutting gate: Grinding wheel cutting gate allowance 2mm (fine cutting allowance 5mm); 2) Shot blasting: 0.2mm steel shot blasting for 30 minutes, the residual sand removal rate is 99.5%; 3) Passivation treatment: Immerse in HNO3:HF:H2O=6:5:5 mixture (60℃) for 3 minutes, rinse with water three times and then blow dry; 4) Heat treatment: sealed annealing in an iron box (covered with charcoal), keeping warm at 650℃ for 2 hours, cooling in the furnace to 600℃ and then air cooling, hardness HB185±3 (tested by Brinell hardness tester).
[0028] Table 1 Comparison of the effects of existing aviation thin-walled castings (material Z22-1 cast iron) and Example 1
[0029] Example 2: Medical device components (made of 316L stainless steel) (1) Wax model preparation 1) Wax treatment: 1. Dehydration in standing barrel I: The old wax liquid is placed at 90℃ for 6 hours, and the sediment at the bottom is discharged. The free water content is reduced to 1.5%; 2. Evaporation in water removal barrel: the temperature is raised to 120℃, mechanical stirring (speed 45r / min) is carried out for 10 hours, and the water content of the wax liquid after evaporation is 0.07%; 3. Standing barrel II decontamination: standing at 85℃ for 15 hours, the separation rate of impurity particles is 99% (diameter>50μm); 4. Curing in an incubator: Keep at 54±1℃ for 24 hours, the shrinkage of the wax is 0.4% (test method: ASTM D790).
[0030] 2) Wax mold pressing: injection pressure 4.2MPa, holding time 15 seconds, wax cylinder temperature 54±1℃, wax nozzle temperature 62℃; cooling water temperature 9℃, wax mold surface finish Ra 1.2μm (roughness meter Mitutoyo SJ-410).
[0031] 3) Module welding: wax mold spacing 8mm (12mm for the hole part), inner gate length 10mm, gate cup upper edge 70mm away from wax mold; welding gap rate 0.3% (microscope detection), immersed in ZF-301 cleaning agent 3 times (1 second each time), after drying, the wettability of silica sol is qualified.
[0032] (2) Shell preparation 1) Coating preparation: 1. Surface layer: 10kg silica sol + 35kg zircon powder, viscosity 55 seconds (4# flow cup, GB / T 1723); 2. Transition layer: 10kg silica sol + 16kg powder, viscosity 20 seconds; 3. Back layer: 10kg silica sol + 14kg powder, viscosity 13 seconds.
[0033] 2) Layered shell making: 1. Surface layer: Sprinkle 50 mesh zircon sand (particle size distribution 30-70 mesh), dry for 7 hours (humidity 60%, temperature 24±1℃); 2. Transition layer: sprinkle 60 mesh sand (particle size 40-70 mesh) and dry for 9 hours; 3. Back layer: sprinkle 16 mesh sand (10-20 mesh) and dry for 14 hours; 4. Sealing layer: Silica sol (viscosity 7 seconds) seals surface pores.
[0034] (3) Dewaxing and roasting 1) High-pressure steam dewaxing: steam pressure 0.75 MPa, dewaxing time 6 minutes, wax residue 0.02% (gravimetric detection); 2) Firing: Keep at 1195℃ for 40 minutes, the shell is rose-colored and has no cracks (visual and penetrant testing).
[0035] (4) Melting and pouring 1) Alloy smelting: 316L stainless steel (C≤0.03%, Cr 16.5%, Ni 10%), smelting temperature 1620℃; after refining, add 0.15% silicon calcium alloy for deoxidation.
[0036] 2) High temperature casting: mold shell temperature 800℃, pouring pressure 0.35MPa; casting grain size ASTM grade 7 (metallographic examination), free of inclusion defects.
[0037] (5) Post-processing 1) Alkali blasting and sand removal: 720℃ alkali solution treatment for 25 minutes, the residual sand removal rate in the cavity is 99.8%; 2) Passivation treatment: immersion in HNO3:HF:H2O mixture (60℃) for 4 minutes, the surface Cr2O3 film thickness is 0.8μm (XRD detection); 3) Heat treatment: solution treatment at 1050℃ and water quenching, hardness HRB 85±2 (tested by Brinell hardness tester).
[0038] Table 2 Comparison of the effects of existing medical device components (material 316L stainless steel) and Example 2
[0039] Example 3: Automobile engine cylinder block (made of QT500-7 ductile iron) (1) Wax model preparation 1) Wax treatment: 1. Dehydration in standing barrel I: The old wax liquid is placed at 88°C for 7 hours, and the sediment at the bottom is drained, and the free water content is reduced to 1.3%; 2. Evaporation in a water removal bucket: temperature 115°C, mechanical stirring (speed 35r / min) for 11 hours, the water content of the wax liquid after evaporation is 0.09%; 3. Standing barrel II decontamination: Standing at 82℃ for 14 hours to separate impurity particles (diameter > 50μm); 4. Curing in an incubator: Keep at 54±1℃ for 26 hours, the shrinkage of the wax is 0.42% (test method: ASTM D790).
[0040] 2) Wax mold pressing: injection pressure 4.2MPa, holding time 8 seconds, wax cylinder temperature 55±1℃, wax nozzle temperature 58℃; cooling water temperature 9℃, dimensional error of the wax mold after demolding ±0.1mm (tested by three-coordinate measuring machine); no burrs or depressions on the surface, smoothness Ra 1.8μm (tested by roughness meter).
[0041] 3) Module welding: wax mold spacing 7mm (10mm in the area with reinforcement ribs), inner gate length 12mm, gate cup upper edge 70mm away from wax mold; welding gap rate 0.3% (microscope detection), immersed in ZF-301 cleaning agent 3 times (1 second each time), after drying, the silica sol wettability is qualified.
[0042] (2) Shell preparation 1) Coating preparation: 1. Surface layer: 10kg silica sol (S830 type) + 34kg zircon powder, flow cup viscosity 53 seconds (4# flow cup, GB / T1723); 2. Transition layer: 10kg silica sol (S1430 type) + 17kg powder, viscosity 22 seconds; 3. Back layer: 10kg silica sol + 15kg powder, viscosity 14 seconds.
[0043] 2) Layered shell making: 1. Surface layer: Sprinkle 80 mesh zircon sand (particle size distribution 80-120 mesh), dry for 6 hours (humidity 55%, temperature 24±1℃); 2. Transition layer: sprinkle 50 mesh sand (particle size 40-70 mesh) and dry for 8 hours; 3. Back layer: sprinkle 30 mesh shop sand (particle size 16-30 mesh) and dry for 12 hours; 4. Sealing layer: Silica sol (viscosity 7 seconds) seals the surface pores, and the drying time is ≥10 hours.
[0044] (3) Dewaxing and roasting 1) High-pressure steam dewaxing: steam pressure 0.65 MPa, dewaxing time 7 minutes, wax residue 0.04% (gravimetric detection); 2) Firing: Keep at 1150℃ for 30 minutes, the shell will be white and free of cracks (visual and penetrant inspection).
[0045] (4) Melting and pouring 1) Alloy melting: 1. Charge ratio: QT500-7 ductile iron (C 3.6%, Si 2.8%, Mg 0.04%), melting temperature 1520±10℃; 2. Spheroidization treatment: Add 1.2% (mass fraction) of spheroidizing agent and the spheroidization reaction time is 3 minutes.
[0046] 2) High temperature pouring: mold shell temperature 780℃, pouring pressure 0.3MPa, covered with graphite powder for shrinkage feeding; casting spheroidization rate 90% (metallographic examination, ASTM A247 standard), no shrinkage defects.
[0047] (5) Post-processing 1) Cutting gate: Grinding wheel cutting gate allowance 2mm (fine cutting allowance 5mm); 2) Shot blasting: 0.2mm steel shot blasting for 25 minutes, surface hardness HB210 (Brinell hardness tester); 3) Annealing: sealed annealing in an iron box (covered with charcoal), 720℃ for 2 hours, furnace cooled to 600℃ and then air cooled, hardness HB195±5; 4) Machining: The machining allowance is reduced from 3mm in traditional processes to 1.5mm, and the material utilization rate is increased by 40%.
[0048] Table 3 Comparison of the effects of the existing automobile engine cylinder block (material QT500-7 ductile iron) and Example 3
[0049] The embodiments of the present invention show that by optimizing the wax pattern processing, shell preparation and post-processing processes, the casting quality and production efficiency are significantly improved, and it has wide application value in the fields of aviation, medical care, automobiles, etc.
[0050] The above description is only a preferred embodiment of the present invention, but the scope of implementation of the present invention is not limited to the embodiment shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the spirit covered by the description, should be within the scope of protection of the present invention.
Claims
1. A silica sol precision casting process, characterized in that: The following steps are involved: (1) Preparation of wax molds: including wax material processing, wax mold pressing, mold welding and mold cleaning; the specific steps of the wax material processing are: the old wax liquid recovered from dewaxing is subjected to dehydration treatment in a static barrel I, stirring and evaporating dehydration in a water removal barrel, and decontamination treatment in a static barrel II, and finally kept warm in an insulated box; the process parameters of the wax mold pressing are: injection pressure 4.2MPa, holding time 5-15s, wax cylinder temperature 54±2℃, wax nozzle temperature 57-64℃, cooling water temperature <10℃; (2) Shell preparation: including coating preparation and layered shell making; the layered shell making includes coating the surface layer with zircon sand, coating the transition layer with upper sand, coating the back layer with coarse-grained upper sand and sealing treatment; (3) Dewaxing and shell firing: Use high-pressure steam dewaxing, steam pressure 0.6-0.75MPa, dewaxing time 6-8min; firing temperature 1150-1195℃, holding time ≥30min; (4) Melting and pouring: including alloy melting and high temperature pouring, melting temperature 1580-1600℃, pouring temperature 700-850℃; (5) Post-processing: including gate cutting, shot blasting, passivation and heat treatment; (6) Casting correction and surface finishing: Use hot correction or cold correction tooling to correct deformation, and use a sanding machine to grind the surface until it is smooth.
2. The silica sol precision casting process according to claim 1, characterized in that: In step (1), the specific parameters of the wax material treatment are: the treatment temperature of the standing barrel I is 85-90°C, the standing time is 6-8h, the stirring temperature of the water removal barrel is 110-120°C, the stirring time is 10-12h, the treatment temperature of the standing barrel II is 80-85°C, the standing time is ≥12h, the temperature of the insulation box is 54±2°C, and the insulation time is ≥24h.
3. The silica sol precision casting process according to claim 1, characterized in that: In step (1), the module welding requires that the wax mold spacing is 6-8mm, the inner gate length is 8-12mm, and the distance between the upper edge of the gate cup and the wax mold after welding is ≥60mm; the module is cleaned by dipping in ZF-301 cleaning agent and blown dry after passing the wetting test.
4. The silica sol precision casting process according to claim 1, characterized in that: In step (2), the coating ratio is: surface coating: silica sol and zircon powder are mixed in a mass ratio of 10: (30-36), and the flow cup viscosity is 50±5s; Transition layer coating: silica sol and upper shop powder are mixed in a mass ratio of 10:(16-17), and the flow cup viscosity is 20±2s; back layer coating: silica sol and upper shop powder are mixed in a mass ratio of 10:(14-15), and the flow cup viscosity is 13±1s.
5. The silica sol precision casting process according to claim 1, characterized in that: In step (2), the process parameters of the layered shell making are: the surface layer sanding particle size is 80-120 mesh zircon sand, the drying time is ≥6h, the transition layer sanding particle size is 50-100 mesh zircon sand or 40-70 mesh upper sand, the drying time is ≥8h, the back layer sanding particle size is 16-30 mesh upper sand, and the drying time is ≥12h.
6. The silica sol precision casting process according to claim 1, characterized in that: In step (4), the slag-forming agent for alloy smelting has the same properties as the furnace lining material, and a covering agent is used to compensate for shrinkage during pouring, and the covering agent is dry charcoal or graphite powder.
7. The silica sol precision casting process according to claim 1, characterized in that: In step (5), the passivation treatment uses a mixture of HNO3:HF:H2O=6:5:5, the temperature is 55-65°C, and the immersion time is 2-5min; the heat treatment is iron box sealed annealing, the annealing temperature is set according to the casting material, and the furnace is cooled to 600°C and then air-cooled.
8. The silica sol precision casting process according to claim 1, characterized in that: In step (6), the residual height of the gate after surface finishing is: flat surface <0.2mm, curved surface <0.1mm; the residual sand in the complex inner cavity is removed by alkali explosion process, the alkali solution temperature is ≥700℃, and the processing time is ≥20min.